Performance variation according to anode-embedded orientation in a sediment microbial fuel cell employing a chessboard-like hundred-piece anode - An, Junyeong; Nam, Jonghyun; Kim, Bongkyu; Lee, Hyung-Sool; Kim, Byung Hong; Chang, In Seop (ELSEVIER SCI LTD, 2015)
The effect of two different anode-embedding orientations, lengthwise-and widthwise-embedded anodes was explored, on the performance of sediment microbial fuel cells (SMFCs) using a chessboard anode. The maximum current densities and power densities in SMFCs having lengthwise-embedded anodes (S-LA1-S-LA10) varied from 38.2 mA/m(2) to 121 mA/m(2) and from 5.5 mW/m(2) to 20 mW/m(2). In comparison, the maximum current densities and maximum power densities in SMFCs having anodes widthwise-embedded between 0 cm to 8 cm (S-WA2-S-WA5) increased from 82 mA/m(2) to 140 mA/m(2) and from 14.7 mW/m(2) to 31.1 mW/m(2) as the anode depth became deeper. Although there was a difference in the performance among S-WA5-S-WA10, it was considered negligible. Hence, it is concluded that it is important to embed anodes widthwise at the specific anode depths, in order to improve of SMFC performance. Chessboard anode used in this work could be a good option for the determination of optimal anode depths. (C) 2015 Elsevier Ltd. All rights reserved.